2013
DOI: 10.2215/cjn.11181012
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Urine Phosphorus Excretion and Mortality and Cardiovascular Events

Abstract: SummaryBackground and objectives Higher morning serum phosphorus has been associated with cardiovascular disease (CVD) in patients with or without CKD. In patients with CKD and a phosphorous level .4.6 mg/dl, the Kidney Disease Improving Global Outcomes guidelines recommend dietary phosphorus restriction. However, whether phosphorus restriction influences serum phosphorus concentrations and whether dietary phosphorus is itself associated with CVD or death are uncertain.Design, setting, participants, & measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 32 publications
5
35
1
1
Order By: Relevance
“…A recent report of 880 adults from the Heart and Soul Study, described an association between higher urinary phosphate excretion with lower risk of cardiovascular events and a non‐significant association with mortality . One quarter of the cohort in this study had CKD and analysis of FGF23 levels revealed an association with mortality which was modified by FEPi .…”
Section: What Happens In Ckd?mentioning
confidence: 51%
“…A recent report of 880 adults from the Heart and Soul Study, described an association between higher urinary phosphate excretion with lower risk of cardiovascular events and a non‐significant association with mortality . One quarter of the cohort in this study had CKD and analysis of FGF23 levels revealed an association with mortality which was modified by FEPi .…”
Section: What Happens In Ckd?mentioning
confidence: 51%
“…In the Heart and Soul study, an observational study of 880 adults with a history of coronary heart disease, 24-h urine phosphorus excretion was not associated with mortality (third tertile versus first tertile aHR 0.78; 95% CI, 0.56–1.07) (124). However, data from this study suggest there may be serious issues with using 24-h urine phosphorus to estimate habitual phosphorus intake.…”
Section: Urine Phosphorus Excretion and Adverse Outcomesmentioning
confidence: 99%
“…We found that more patients with Mg levels of 2.9 mg/dL or higher were taking oral Mg (Supplemental Table 2, available online at http://www.mayoclinic proceedings.org). In the fully adjusted model (model 4, which included hyperphosphatemia [implicated in mortality [26][27][28] ]), the risk for hospital mortality and being discharged to a care facility was increased when Mg levels were 2.3 mg/dL or higher. The mortality risk increased progressively with increasing Mg level (Figure 3, B).…”
Section: Clinical Outcomesmentioning
confidence: 99%